Stoichiometric homeostasis predicts plant species dominance, temporal stability, and responses to global change. Issue 9 (1st September 2015) - Yu, Qiang; Wilcox, Kevin; Pierre, Kimberly La; Knapp, Alan K.; Han, Xingguo; Smith, Melinda D.
Abstract : Why some species are consistently more abundant than others, and predicting how species will respond to global change, are fundamental questions in ecology. Long‐term observations indicate that plant species with high stoichiometric homeostasis for nitrogen ( H N ), i.e., the ability to decouple foliar N levels from variation in soil N availability, were more common and stable through time than low‐ H N species in a central U.S. grassland. However, with nine years of nitrogen addition, species with high H N decreased in abundance, while those with low H N increased in abundance. In contrast, in climate change experiments simulating a range of forecast hydrologic changes, e.g., extreme drought (two years), increased rainfall variability (14 years), and chronic increases in rainfall (21 years), plant species with the highest H N were least responsive to changes in soil water availability. These results suggest that H N may be predictive of plant species success and stability, and how plant species and ecosystems will respond to global‐change‐driven alterations in resource availability.